ACR appropriateness criteria® nasal cavity and paranasal sinus cancers. Issue 3 (29th December 2016) - Siddiqui, Farzan; Smith, Richard V.; Yom, Sue S.; Beitler, Jonathan J.; Busse, Paul M.; Cooper, Jay S.; Hanna, Ehab Y.; Jones, Christopher U.; Koyfman, Shlomo A.; Quon, Harry; Ridge, John A.; Saba, Nabil F.; et al.
Abstract: The American College of Radiology (ACR) Appropriateness Criteria are evidence‐based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer‐reviewed journals and the application of well‐established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness of imaging and treatment procedures for specific clinical scenarios. In those instances where evidence is lacking or equivocal, expert opinion may supplement the available evidence to recommend imaging or treatment. Here, we present the Appropriateness Criteria for cancers arising in the nasal cavity and paranasal sinuses (maxillary, sphenoid, and ethmoid sinuses). This includes clinical presentation, prognostic factors, principles of management, and treatment outcomes. Controversies regarding management of cervical lymph nodes are discussed. Rare and unusual nasal cavity cancers, such as esthesioneuroblastoma and sinonasal undifferentiated carcinomas, are included. © 2016 American College of Radiology. Head Neck, 2016 © 2016 Wiley Periodicals, Inc. Head Neck 39: 407–418, 2017